Biomaterials used for tissue engineering of barrier-forming cell monolayers in the eye - Sasseville, Samantha; Karami, Samira; Tchatchouang, Ange; Charpentier, Pascale; Anney, Princia; Gobert, Delphine; Proulx, Stéphanie (Frontiers in Bioengineering and Biotechnology, 2023)
Cell monolayers that form a barrier between two structures play an important role for the maintenance of tissue functionality. In the anterior portion of the eye, the corneal endothelium forms a barrier that controls fluid exchange between the aqueous humor of the anterior chamber and the corneal stroma.This monolayer is central in the pathogenesis of Fuchs endothelial corneal dystrophy (FECD). FECD is a common corneal disease, in which corneal endothelial cells deposit extracellular matrix that increases the thickness of its basal membrane (Descemet's membrane), and forms excrescences (guttae). With time, there is a decrease in endothelial cell density that generates vision loss. Transplantation of a monolayer of healthy corneal endothelial cells on a Descemet membrane substitute could become an interesting alternative for the treatment of this pathology. In the back of the eye, the retinal pigment epithelium (RPE) forms the blood-retinal barrier, controlling fluid exchange between the choriocapillaris and the photoreceptors of the outer retina. In the retinal disease dry age-related macular degeneration (dry AMD), deposits (drusen) form between the RPE and its basal membrane (Bruch's membrane). These deposits hinder fluid exchange, resulting in progressive RPE cell death, which in turn generates photoreceptor cell death, and vision loss. Transplantation of a RPE monolayer on a Bruch's membrane/choroidal stromal substitute to replace the RPE before photoreceptor cell death could become a treatment alternative for this eye disease. This review will present the different biomaterials that are proposed for the engineering of a monolayer of corneal endothelium for the treatment of FECD, and a RPE monolayer for the treatment of dry AMD.